Weed pressure across sequential plantings of industrial fiber hemp (Cannabis sativa L.) produced in the mid‐Atlantic - Erin A. Myers; Kurt M. Vollmer; Andrew G. Ristvey; Nicole M. Fiorellino (Agrosystems, Geosciences & Environment, 2025)
Abstract With the lack of herbicides approved for use in industrial hemp (Cannabis sativa L.) production, it is important to determine which cultural practices can be utilized to manage weeds. With the general quick growth and dense stand to shade soil surface, hemp produced for fiber, when established early, has the potential to compete with weed populations and prevent weed proliferation. The objectives of this study were to evaluate how a planting date continuum of fiber hemp impacted weed pressure under two growing scenarios, continuous hemp and weed competition or early season weed removal, to inform future research and provide production guidance to hemp producers. Pre‐plant tillage and herbicide applications to establish fiber hemp in the present study resulted in plots that were generally weed‐free. Data collected on weed biomass and species present supported that planting and harvest dates did not significantly impact weed pressure, and that weeds present were also biologically insignificant relative to the fresh fiber hemp yield measured. When planting fiber hemp, producers should focus on proper field location and preparation, timely planting, and correct seeding rates to mitigate weed pressures in the interim to post‐emergence herbicide approvals.